Implementation of the 7 Habits of Great Indonesian Children Program to Realize a Character-Based School Culture at SMPN 3 Baleendah - Waska Warta; Ana Suryana; Mulyati; Rina Nuraeni (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to analyze the effectiveness of school management in implementing the "7 Habits of Great Indonesian Children Program" as a strategy for engineering a character-based school culture. Amidst the moral crisis among students and the challenges of digital disruption, the gap between character education policies and operational practices in schools has become a crucial issue. Using a descriptive qualitative approach with a case study design at SMPN 3 Baleendah, Bandung Regency, this study examines managerial dynamics through the lens of Deming's PDCA (Plan, Do, Check, Act) cycle. Data were collected through participant observation, in-depth interviews, and documentation studies, then analyzed using Miles and Huberman's interactive model. The research findings indicate that: (1) The Planning stage of the 7 Habits Program at SMPN 3 Baleendah is not merely an administrative task but serves as a crucial foundation for the school’s transformation. The planning is carried out in a structured, data-based, and participatory manner, ensuring that the program truly aligns with students’ character-building needs and complies with national policies; (2) The Do stage was driven by the instructional exemplary leadership and integration of the hidden curriculum; (3) The Check stage applied fact-based management that revealed the gap between public and private character; and (4) The Act stage ensured sustainability through external correction mechanisms and internal standardization (refreezing). The study concluded that the integration of PDCA quality management discipline with transformational leadership is a determining variable in realizing a character-based school ecosystem.